Analisis Spasial Tingkat Intrusi Air Laut Pada Sumur Bor Di Kota Kendari - Sulpiana Sulpiana; Iradat Salihin; Fitra Saleh; Nurgiantoro Nurgiantoro; Al Firman (Universitas Halu Oleo, 2023)
In simple terms, water is one of the natural resources that is very important and valuable for the survival of humans and other living things. The aims of this study are to: (1) Determine the distribution of the use of boreholes; (2) Knowing the level of sea water intrusion on ground water in Kendari City. The analytical methods used are: (1) Spatial interpolation analysis to create a map of the distribution of boreholes using the Arcgis 10.8 application; (2) Quality assessmentborehole water with seawater intrusion based on DHL values. The results of this study include: (1) The distribution of the use of drilled wells is spread throughout the Kendari City area with the highest distribution being in Poasia and Kambu Districts; (2) The groundwater condition of Kendari City has been very high intrusion with an area of 15,573,441.57 acre or 6%, these conditions are in Abeli District, Kendari District, West Kendari District, Mandonga District, Nambo District and Poasia District. The condition of groundwater with moderate intrusion level is 16% or 42.465,795.75 acre, the area with unintruded groundwater is in Baruga District.Keywords: Spatial Analysis, Seawater Intrusion, Deep well